Identifying patient safety research priorities in Estonia: results of a Delphi consensus study - Freimann Tiina; Polluste Kaja; Calsbeek Hilly; Kangasniemi Mari; Lember Margus; Orrego Carola; Vall-Roque Helena; van Tuijl Anne; Starkopf Joel (BMJ PUBLISHING GROUP, 2022)
Patient safety research aims to create new knowledge and find evidence-based solutions to improve patient safety and reduce avoidable adverse events in healthcare.1 More than a decade ago, the WHO recommended that all countries identify, analyse and prioritise areas where patient safety research could reduce avoidable harm and improve healthcare systems.2 However, only a few articles about this topic have been published,3–6 and only one examined research priorities for patient safety at the national level.6
The Patient Safety Research and Development Centre (PSR&DC) at the Faculty of Medicine of the University of Tartu plays a national role in introducing research-based patient safety practices in Estonia. Its work group previously identified patient safety research in Estonia as limited, fragmented and unsystematic.7 There is not enough reliable information to support patient safety practices in the Estonian healthcare system. As a part of the Patient Safety Research and Development Strategy 2022–2026 by PSR&DC, this study aimed to collect expert judgements and determine a consensus for patient safety research priorities in Estonia.